1978
DOI: 10.1242/jcs.30.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Membranes in lupin root nodules: II. preparation and properties of peribacteroid membranes and bacteroid envelope inner membranes from developing lupin nodules

Abstract: Peribacteroid membranes and bacteroid envelope inner membranes have been isolated from developing lupin nodules. Isolation of the peribacteroid membranes was achieved by first preparing membrane-enclosed bacteroids free from other plant organelles or membranes. The peribacteroid membranes were then released by osmotic shock and purified by centrifugation to equilibrium on sucrose gradients. The bacteroids were broken in a pressure cell and the bacteroid envelope inner membranes were isolated using sucrose grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We could not detect any immunoreactive material inside the isolated membrane envelopes enclosing the bacteroids (Verma et al, 1978). Robertson et al (1978) showed by isolating the bacteroids enclosed in the membrane envelope from Lupin nodules in the presence of ferritin that these envelopes do not open and reseal during fractionation, thereby leaking all their Lb contents. These data, along with analyses of the primary translation product of Lb mRNA, conclusively prove that Lb is a cytoplasmic protein of the host cell and it does not cross the membrane envelope enclosing the bacteroids (see Verma & Bal 1976.…”
Section: Discussionmentioning
confidence: 82%
“…We could not detect any immunoreactive material inside the isolated membrane envelopes enclosing the bacteroids (Verma et al, 1978). Robertson et al (1978) showed by isolating the bacteroids enclosed in the membrane envelope from Lupin nodules in the presence of ferritin that these envelopes do not open and reseal during fractionation, thereby leaking all their Lb contents. These data, along with analyses of the primary translation product of Lb mRNA, conclusively prove that Lb is a cytoplasmic protein of the host cell and it does not cross the membrane envelope enclosing the bacteroids (see Verma & Bal 1976.…”
Section: Discussionmentioning
confidence: 82%
“…Rhizobia colonize the ITs which grow through root cells, ultimately reaching the nodule primordium. The bacteria are then budded off surrounded by a plant-made membrane into plant cells in which they fix nitrogen using carbon supplied by the plant [ 5 ]. Genetic studies in Lotus japonicus and Medicago truncatula have identified several genes required for IT initiation and formation.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobia attach to root hairs, triggering root-hair curling that entraps rhizobia which induce localized cell-wall degradation and rearrangement of the plant cytoskeleton, contributing to the formation of plant-made tunnel-like structures called the infection threads (ITs) (Gage, 2004). Rhizobia colonize the ITs which grow through root cells, ultimately reaching the nodule primordium; the bacteria are then budded off surrounded by a plant-made membrane into plant cells in which they fix nitrogen using carbon supplied by the plant (Robertson et al, 1978). Genetic studies in Lotus japonicus and Medicago truncatula have identified several genes required for IT initiation and formation.…”
Section: Introductionmentioning
confidence: 99%